Effect of Mo addition on the pitting resistance of TiMn alloys in Hanks’ solution - Tanji, Ayoub (Elsevier Ltd, 2021)
A family of TiMn alloys having a comparable mechanical property to Ti6Al4V alloy was developed for biomedical applications. Addition of 3–4 wt% Mo was found to improve corrosion resistance of the alloys to a level of that of commercial pure Ti. The effect of Mo to the electrochemical parameters of the passive film was not yet clarified. This work evaluated the effect of Mo on pitting resistance of Ti6Mn4Mo (TiMnMo) alloy in Hanks’ solution using electrochemical techniques combined with SEM, AFM and XPS analyses. Electrochemically, the TiMnMo demonstrated a higher resistance to uniform corrosion than Ti6Mn (TiMn) with a re-passivation and restoration ability against pitting corrosion which was not observed on TiMn. The TiMnMo showed a non-diffusional corrosion characteristic due to a denser passive film than that of TiMn. The SEM and AFM observation revealed a more severe pitting formation on TiMn than on TiMnMo. The XPS analysis confirmed the presence of Mo and Mn oxides that reinforced the TiO2 matrix. The mechanism of the different passivation behaviors of the two alloys is described according to the point defect model that based on the balance of kinetics of the oxide layer growth and dissolution reactions.